Multivariate effect gradients driving forest demographic responses in the Iberian Peninsula - Coll, Marta; Penuelas, Josep; Ninyerola, Miquel; Pons, Xavier; Carnicer, Jofre (Forest Ecology and Management, 2013)
A precise knowledge of forest demographic gradients in the Mediterranean area is essential to assess future impacts of climate change and extreme drought events. Here we studied the geographical patterns of forest demography variables (tree recruitment, growth and mortality) of the main species in Spain and assessed their multiple ecological drivers (climate, topography, soil, forest stand attributes and tree-spe- cific traits) as well as the geographical variability of their effects and interactions. Quantile modeling analyses allowed a synthetic description of the gradients of multiple covariates influencing forest demog- raphy in this area. These multivariate effect gradients showed significantly stronger interactions at the extremes of the rainfall gradient. Remarkably, in all demographic variables, qualitatively different levels of effects and interactions were observed across tree-size classes. In addition, significant differences in demographic responses and effect gradients were also evident between the dominant genus Quercus and Pinus. Quercus species presented significantly higher percentage of plots colonized by new recruits, whereas in Pinus recruitment limitation was significantly higher. Contrasting positive and negative growth responses to temperature were also observed in Quercus and Pinus, respectively. Overall, our results synthesize forest demographic responses across climatic gradients in Spain, and unveil the inter- actions between driving factors operating in the drier and wetter edges.
The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: Forest demography; Growth; Macroecology; mortality; Quantile modeling; Recruitment